2013
DOI: 10.1055/s-0033-1356485
|View full text |Cite
|
Sign up to set email alerts
|

Palivizumab Prophylaxis: Does It Have Any Influence on the Growth and Development of the Infants?

Abstract: Palivizumab reduced the incidence of lower respiratory tract infections and hospitalizations due to RSV both in the year of prophylaxis and in the following year. However, this decrease did not have any impact on the development of infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 8 publications
1
19
0
Order By: Relevance
“…Moreover, palivizumab showed a favorable safety profile . Another RCT confirmed that the incidence of hospitalization due to RSV was lower in palivizumab recipients both at the year of prophylaxis and in the following year ( P = 0.001, OR 1.32, 95%CI 1.11–1.57) …”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Moreover, palivizumab showed a favorable safety profile . Another RCT confirmed that the incidence of hospitalization due to RSV was lower in palivizumab recipients both at the year of prophylaxis and in the following year ( P = 0.001, OR 1.32, 95%CI 1.11–1.57) …”
Section: Resultsmentioning
confidence: 90%
“…2 Another RCT confirmed that the incidence of hospitalization due to RSV was lower in palivizumab recipients both at the year of prophylaxis and in the following year (P ¼ 0.001, OR 1.32, 95%CI 1.11-1.57). 14 Severe RSV bronchiolitis has been associated with an increase in subsequent rates of early wheezing, asthma, and possibly allergic sensitization later in life. Palivizumab prevented the recurrent wheeze subsequent to RSV infection: a significant reduction in wheezing days during the first year of life (1.8% palivizumab group vs. 4.5% placebo group), even after the end of palivizumab treatment was reported.…”
Section: Efficacy Of Seasonal Prophylaxis With Palivizumab In Pretermmentioning
confidence: 99%
“…
Fig. 2 RSV-related hospitalization rates in the large randomized controlled trials: a IMpact-RSV [ 24 ], b Carbonell-Estrany et al [ 70 ], c MAKI [ 30 ], d Tavsu et al [ 31 ], e Cardiac [ 23 ], and f Feltes et al [ 71 ] studies. Relative reduction rate compared with placebo is shown as ↓%.
…”
Section: Resultsmentioning
confidence: 99%
“…More recently, Tavsu et al [ 31 ] conducted a study from 2009 to 2011 in 80 infants with a GA of <32 weeks in Turkey. These infants were randomized to receive prophylaxis with palivizumab (study group, n = 39) or no prophylaxis (control group, n = 41).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation